Fracture risk and treatment in chronic kidney disease. Issue 3 (May 2018) - Connelly, Kelsey; Collister, David; Tangri, Navdeep
Abstract : Purpose of review: Chronic kidney disease (CKD) is associated with the development of mineral bone disorder (MBD), osteoporosis, and fragility fractures. The purpose of this review is to provide an update on recent findings in the diagnosis and treatment of osteoporosis in patients with CKD. Recent findings: Multiple observational studies have shown that bone mineral density measurement using DEXA is equally predictive in CKD stages 1–3, as in the general population. Post hoc analyses from randomized trials of bisphosphonates, SERM, RANKL inhibitors and PTH agonists all suggest equal efficacy in mild–moderate CKD. A recent systematic review also found evidence for efficacy of bisphosphonates in patients with a kidney transplant. Summary: Bone mineral density measurement using DEXA is accurate in patients with CKD stages 1–3 and should be considered to guide treatment of osteoporosis. Current treatments are unaffected by mild-to-moderate decline in kidney function, and physicians should use bisphosphonates and other osteoporosis treatments in this population, whenever indicated. Studies evaluating the optimal diagnostic and management strategy in patients with CKD stages (G4-5D) are needed.